Design and modelling of an anti-buckling compliant universal joint with a compact configuration. (February 2021) - Li, Shiyao; Hao, Guangbo; Wright, William M.D.
Highlights: We present a new compact complaint U-joint with axial anti-buckling in bidirection. We improve the compliance matrix of a generic sheet. We derive the generalized compliance matrix of the joint about its centroid. We analyse the effect of sheet geometry on the joint's precision and motion range. We analyse the nonlinearities of the joint by nonlinear finite element analysis. Abstract: This paper presents a new compliant universal joint using four identical generic sheet flexures (short sheets) and a long wire beam. The compliant joint is compact and in mirror symmetry, and is robust to axial buckling in bi-direction. The compliance matrix of the generic sheet, including a straight sheet and an elliptical-arc-fillet (EAF) sheet, is improved at first. Then a normalization-based analytical model of the universal joint is derived, followed by mobility identification of the joint. The relationships between the straight-sheet joint's compliance and the length, width and thickness of the sheet are analysed quickly using the analytical model. The linear finite element analysis (FEA) is further applied to verify the analytical model for different joints. Given different geometrical parameters of the EAF sheet, their effects on the parasitic motion and the maximum deformation of the joint are elaborated. Nonlinear FEA is used to analyse nonlinearities of the joint consisting of straight sheets and a round wire beam, including the large deformation, load-dependent effect, and axial anti-buckling. Experimental results verify the accuracy of the derived analytical models and confirm the successful design of the proposed universal joint.